New Mammutidae material from Yushe Basin (southeastern Shanxi, China) and their implications for Mammut evolution - Xiao-Xiao Zhang; Xue-Wen Kuang; Jian-Yu Gong; Yun-Xia Zhang; Hui-Fang Liu; Dan Li; Yu Li; Shi-Qi Wang (Palaeoworld, 2026)

Methane production from caproic acid fermentation residuals of food waste in anerobic dynamic membrane bioreactor: A promising route for organic waste valorization - Yunhui Pu; Jingyun Chen; Dan Xu; Yang Luo; Bujiamu Ayi; Yang Li; Yuting Kuang; Qingyuan Wang; Jialing Tang; Abdelfatah Abomohra (Journal of Environmental Management, 2026)

fNIRS-STCT: A Novel Hybrid Spatial and Temporal CNN and Transformer Network for fNIRS Signal Classification - Li-Dan Kuang; Yi-Xiao Wang; Wenjun Li; Yan Gui (Brain Topography, 2026)

Dual-modified graphitic carbon nitride for enhanced charge carrier separation and transfer towards superior photocatalytic degradation of oxytetracycline - Dan Xu; Heshan Cai; Daguang Li; Feng Chen; Kunkun Hu; Jinhua Zhuang; Xinyao You; Zhuoyan Kuang; Ningyu Tu; Xiaojuan Chen; Xiaoxia Li (Journal of Environmental Chemical Engineering, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Selective extraction of potassium from low K/Na ratio wastewater using a NiHCF-based RCDI device - Dan Li; Qi Kuang; Meng-Yue Zhang; Shu-Jie Hu; Yuan Liu (Journal of Environmental Chemical Engineering, 2026)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Path planning and topology-aided acoustic emission damage localization in high-strength bolt connections of bridges - Dan Li; Jia-Hao Nie; Hao Wang; Tao Yu; Kevin Sze Chiang Kuang (Engineering Structures, 2025)

Multi-objective optimization-based acoustic emission damage location in orthotropic steel decks considering complex wave paths - Jia-Hao Nie; Dan Li; Hao Wang; Tao Yu; Kevin Sze Chiang Kuang (Engineering Structures, 2025)

Pharmacokinetic-pharmacodynamic Modelling of NH600001 in Healthy Subjects and Patients Undergoing Gastroscopy - Yaxin Liu; Yun Kuang; Jie Huang; Dan Jiang; Yajie Cao; Qi Gao; Zifeng Li; Wen Ouyang; Saiying Wang; Qi Pei; Guoping Yang (The AAPS Journal, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Experimental and numerical study on seismic performance of assembled platform canopy with mortise-tenon joints - Yu-zhen Chang; Jiu-yi Kuang; Chong Bai; Yu-jun Cai; Dan-ning Wang; Yuan Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

The pro-absorptive effect of glycosylated zein-fatty acid complexes on fucoxanthin via the lipid transporter protein delivery pathway - Huiying Kuang; Xuan Peng; Yixiang Liu; Dan Li (Food Chemistry, 2024)

Fourteen undescribed steroidal saponins from Solanum capsicoides leaves and their neuroprotective effects - Yan Liu; Xin-Yuan Li; Jia-tong Wu; Han Wang; Xin Meng; Hai-Dan Zou; Juan Pan; Wei Guan; Adnan Mohammed Algradi; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Impact of reclamation projects on water quality in jinmeng bay, China - Cuiping Kuang; Dan Wang; Gang Wang; Jiantao Liu; Xuejian Han; Yan Li (Estuarine, Coastal and Shelf Science, 2024)

The dissolution characteristics of cadmium containing birnessite produced from paddy crusts - Liang Peng; Dan Li; Huijuan Song; Xiaolin Kuang; Qingru Zeng; Hejun Ao (Science of The Total Environment, 2024)

Application of biological soil crusts for efficient cadmium removal from acidic mine wastewater - Xiaolin Kuang; Yiling Hu; Liang Peng; Dan Li; Huijuan Song; Ke Song; Changwu Li; Yuanlong Wang; Shilong He (Journal of Hazardous Materials, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Cadmium accumulation in rice grains is mitigated by duckweed-like hydrophyte through adsorption and increased ammonia nitrogen - Shaoning Chen; Junhui Xu; Liang Peng; Ziyi Cheng; Xiaolin Kuang; Dan Li; Cheng Peng; Huijuan Song (Science of The Total Environment, 2023)

Fertilizer-induced manganese oxide formation enhances cadmium removal by paddy crusts from irrigation water - Xiaolin Kuang; Liang Peng; Ziyi Cheng; Siyan Zhou; Shaoning Chen; Cheng Peng; Huijuan Song; Changwu Li; Dan Li (Journal of Hazardous Materials, 2023)

Construction of a boron nitride nanosheet hybrid for tough, strong, and flame-retardant phenolic resins - Jiongjiong Li; Ying Zhu; Ruohong Bian; Yanqiang Wei; Shuaicheng Jiang; Kuang Li; Xiaona Li; Dan Tian; Xianxu Zhan; Jianzhang Li (Chemical Engineering Journal, 2023)

Exploring the effects of livelihood capital on clean cooking of rural households in the Tibetan region of China - Xin Qiu; Jianjun Jin; Chenyang Zhang; Dan Liu; Lin Li; Foyuan Kuang (Energy and Buildings, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Precipitation-free aluminum-air batteries with high capacity and durable service life - Chaonan Lv; Yixin Li; Yuanxin Zhu; Yuxin Zhang; Jialin Kuang; Dan Huang; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Structure Elucidation and Mechanistic Study of a New Dimeric Degradant in Ropinirole Hydrochloride Extended-Release Tablets - Zijian Kuang; Tianpei Huang; Dan Li; Danna Zhao; Jianyang Jin; Jinsheng Lin; Wenquan Zhu; Wenbin Chen; Min Li; Weiyang Shen (Pharmaceutical Research, 2020)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Distribution of anthropogenic lead estimated by Pb isotopic composition in the upper layers of soil from a mixed forest at Dinghushan, southern China - Yuanwen Kuang; Xiaomin Zhu; Dan Xi; Jiong Li (Journal of Soils and Sediments, 2013)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)